Identity, Politics and Ecology in Postcolonial War-Torn Society: An Interview with Romesh Gunesekera. Issue 3 (3rd July 2021) - Sarkar, Somasree; Karmakar, Goutam
Abstract: The conversation with the Sri Lankan-British novelist, Romesh Gunesekera highlights the complexity of contested issues of home, memory and identity of a South Asian diasporic subject in relation to the political turmoil of a war-torn postcolonial Sri Lanka. The conversation also calls attention to the depletion of the island eco-system in connection with the island's socio-political upheaval and ethnic conflict. The vulnerability of a subject along with his/her eco-political surroundings form the major part of Gunesekera's intricately weaved narratives set in multiple locations across the globe. Gunesekera in the course of the conversation explains the nuances of his narratives and his dynamic characters, inspired by his personal experiences occasionally.